THE ABSURDITY OF TOKUSUKE UTSUGI’S ROLE IN HIS FAMILY AS A POTRAIT OF JAPANESE FAMILY’S CULTURAL CHANGES IN JUNICHIRO TANIZAKI’S DIARY OF A MAD OLD MAN - Desi Tri Cahyaningati (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2014)
Tokusuke as the main characters in Diary of mad old man hasmany conflicts with other members of his family. Thus by understanding the conflicts around him, the writer can get full understanding about the motivation that causes the conflicts in his family. The motivations behindthose conflicts are mostly caused by his blind love to Satsuko. His obsession and his strong sexual desire make him against the whole family. Thus his roles in his family show the cultural changes in Japanese families.